Internet Use Management Program: Its Effects on the Lifestyle of High School Students - Fiseha, Feven Tekeste; Estrada, Miriam Razon (11th International Scholars Conference, 2017)
The study determined the effects of an internet use management program on the lifestyle of high school students. The study utilized the quasi-experimental design using two-group pretest- posttest designs. Fifty one participants in the experimental group were exposed to the four-week Internet Use Management Program while 46 participants in the control group did not undergo any intervention. At baseline, the experimental group had a fair dietary lifestyle and sleeping patterns and poor physical activity. The control group had fair dietary lifestyle and physical activity, and good sleeping patterns. Both groups used the internet moderately. After the intervention, the experimental group exhibited good dietary lifestyle and physical activity. Sleeping pattern was very good and internet use was mild. The experimental group showed a significant difference in their lifestyle while the control group had no significant difference in baseline and endline scores. When the gain scores of both groups were compared, a significant difference was found in their lifestyle, with the experimental group having higher gain scores in dietary lifestyle, physical activity, sleeping pattern and internet use. While there was no significant difference in gain scores when gender was considered. The results of this study suggest that the internet use management program was effective in promoting healthy lifestyle practices in diet, physical activity, sleep and internet use among high school students.